8 - Book Reviews: Thomas R. Black. Evaluating Social Science Research: An Introduction, London, SAGE Publications, 1993, p. 183.: by Kibet A. Ng’etich - Kibet A. Ng'etich (Africa Development, 1995)
Abstract